MANAGING THE PRECOMBINATION PHASE FOR ENHANCED MERGER AND ACQUISITION SUCCESS - NARALOČNIK, Andrej; BERTONCELJ, Andrej (Studia Universitatis Babeș-Bolyai Oeconomica, 2016)
The aim of this paper is to investigate the precombination phase of merger and acquisitions (M&As). The study of two implemented M&A cases in Slovenia shows that the precombination phase and related groups of success factors highly contribute to overall success with M&A. The proposed paradigmatic model may serve as an additional reminder when companies join forces. Study results show that precombination phase considerations lead to the notion of compatibilities and complementarities between combining companies; commonly referred as strategic, organizational and financial ‘fit’ and that indicated groups of strategic, financial and organizational success factors can be classified towards such ‘fit’ areas. JEL Classification: E 22, D 23, G 34